The Du Pont Building at the Exposition, New York World's Fair (Curt Teich & Co.)
A series of giant retorts and vessels, mounting 100 feet into the sky and filled with gases and liquids in ever-changing colors, emphasizes the importance of chemistry in the Du Pont Company's exhibit. Walter Dorwin Teague is the designer and A.M. Erickson the engineer.